Association between serum vitamin D and refractive status in United States adolescents: A cross-sectional study - Li, Yanqing; Hu, Pengcheng; Wu, Xianhui; Zou, Qian; Liu, Xiaozhu; Liu, Jialing; Fu, Yuxian (Frontiers in Nutrition, 2022)
Purpose We performed this study to determine the relationship between serum vitamin D levels and refractive status in adolescents aged 12–19 years. Methods Cross-sectional study using the National Health and Nutrition Examination Survey (NHANES) database from 2001 to 2006. We used weighted multivariate linear regression models to assess the association between serum vitamin levels and adolescent refractive status and then built a smooth curve fitting to investigate their internal non-linear relationships. Finally, subgroup analysis was performed according to gender, and the threshold effect of serum vitamin D levels on spherical equivalent degree was analyzed using a two-piecewise linear regression model. Result A total of 5,901 adolescents aged 12 to 19 years were included in this study. After adjusting for all confounding factors, the multiple linear regression model showed no significant correlation between adolescent spherical equivalent degree and serum vitamin D [0.0019 (−0.0018, 0.0046)]. However, smooth curve fitting analysis showed an inverted U-shaped curve relationship between spherical equivalent degree and serum vitamin D levels in adolescents (turning point: 58.1 nmol/L). In analyses by gender subgroup, this inverted U-shaped relationship was found to be more pronounced in female adolescents (turning point: 61.6 nmol/L). Conclusion Our results suggest that the correlation between refractive status and serum vitamin D in adolescents differs by gender. When serum vitamin D concentrations were <61.6 nmol/L in female adolescents and <53.2 nmol/L in male adolescents, the spherical equivalent degree showed a positive correlation with serum vitamin D levels. However, there was no significant correlation when adolescent vitamin levels exceeded this threshold.